Turkey Iron and Steel Industry Competitiveness and Industry 4.0 - Zehra Vildan Serin; Osman Fidan (Journal of Transportation and Logistics, 2019)
In Turkey in 2018 it produced about 37,3 million tons of steel in the world top ten steel producing countries 8th position. In 2018, exports of iron and steel products amounted to USD 11.5 billion and imports amounted to USD 18.4 billion. This corresponds to 11% of total exports and 8% of total imports. Iron and steel exports and imports are in the third place. In addition, Iron and Steel Sector, automotive, machinery manufacturing, construction, infrastructure, defense, and so on. is the basic industry for the industry. At the end of the study; most steel producing countries and Turkey top 10 iron and steel sector competitive advantages and disadvantages in the world are examined. Competitive advantage for the transition to Industry 4.0 has been studied, using technology and resources effectively to ensure global competitive advantage. “The Global Competitiveness Index 4.0” in Turkey with 62.1 points out of 100 points in 141 countries and ranks 61., China produces 928.3 million tons of 1,808.4 million tons of steel, 51% of which is the world's top steel producer, and the Global Competitiveness Index is ranked 28th with 73.9 points. India is ranked 2nd with 106.5 million tons of steel production and the Global Competitiveness Index is ranked 68th with 61.4 points. Japan ranks 3rd with 104.3 million tons of steel production and the Global Competitiveness Index is ranked 6th with 82.3 points. Ore, scrap, energy-importing Turkey, iron exceed 4.0 applications to provide a competitive advantage to industry in the steel industry will provide a competitive advantage.